Teacher Qualifications, Class Size and Teaching Experience as Predictors of Achievement in Senior Secondary School Physics in Oyo State, Nigeria - Ajadi, Titilayo Adeoye (Papers in Education and Development, 2021)
Abstract This study investigated teacher qualification, class size, and teaching experience as the influencing factors on physics achievement among senior secondary school students. The study adopted the correlational descriptive research design. Ten schools in Oyo State were selected using multistage sampling procedures and a total of 220 secondary school students were used. Three research questions were generated and tested at 0.05 level of significance. Reliable instruments (teachers characteristics scale; r=0.87 and physics achievement test; r=0.81) were used in collecting the data. Data collected were analysed using Pearson Product Moment Correlation Coefficient and Multiple Linear Regression Statistical Tools. It was discovered that there was a significant relationship between class size (Î±=0.201) and teaching experience (Î±=0.727), physics achievement (Î±=0.285) and teacher qualification. Regression analysis revealed that the three independent variables combined accounted for 15.5% (Adj. R2 = .155) variation in the prediction of students' achievement. Based on the findings, it was recommended that most qualified Physics teachers must be allowed teaching physics in Senior Secondary Schools and class size should be reduced to 30 students per class. Keywords: class size, Physics achievement, teacher qualification, teaching experience